Development of a System to Deliver Inhalational Antibiotics to Marmosets - Rachel E. Ireland; Stuart J. Armstrong; Carwyn Davies; James D. Blanchard; Francis Dayton; Igor Gonda; Sarah V. Harding; Michelle Nelson (Antibiotics, 2025)
Background: Inhalational antibiotics have been used effectively to treat chronic diseases such as Pseudomonas aeruginosa infections associated with cystic fibrosis. This approach may enhance treatment options for difficult-to-treat, acute pneumonic diseases. Liposomal encapsulated ciprofloxacin (Lipoquin and/or Apulmiq) has provided protection in murine models of plague, anthrax, Q fever and tularemia. Development of the ability to deliver these drugs to nonhuman primates (NHPs) would enable further extrapolation of the data observed in small animal models of infection to humans. Methods: In this study, the methodology was established to deliver Apulmiq to common marmosets (Callithrix jacchus). Marmosets were anaesthetised with a novel, reversible anaesthetic comprising fentanyl, medetomidine and midazolam (FMM). They were placed into plethysmography tubes with their heads in an exposure chamber. The LC Sprint jet nebuliser or Pari eFlow Rapid nebuliser were used to aerosolise Apulmiq into the exposure chamber. Animals were euthanised after dosing and the concentration of ciprofloxacin was assessed in the plasma and lungs of the animals. Results: Non-compartmental pharmacokinetic analysis determined that a 30 min exposure of drug was required to reach a human-equivalent target dose of 0.8 mg/kg body weight in the lungs. Conclusions: This approach can now be used to assess the efficacy of inhalational liposomal ciprofloxacin in NHP infection models.